The propylene glycol supplementation improves energy metabolism in pregnant sheep - Dos Santos, Rogério Pereira; De Lima Macedo, Gilberto; Da Silva, Simone Pedro; Sousa, Luciano Fernandes; Andrade, Marina Elizabeth Barbosa [UNESP] (My University, 2017)
The objective was to evaluate the effect of propylene glycol inclusion in water pregnant ewes on energy metabolic parameters. We evaluated 28 pregnant ewes which received various levels of propylene glycol (PG) in water. These sheep were distributed in four treatments (0, 1.5, 3.0 and 4.5% PG) in a randomized design in a split plot design. The highest propylene glycol inclusion (3.0 and 4.5%) in the water caused linear increase in blood glucose concentration throughout the gestational period. The blood glucose concentration in sheep receiving 3% propylene glycol in water increased linearly with the increase in the collection period. On the other hand, for the sheep who received 4.5% of propylene glycol response was quadratic. The addition of propylene glycol in the pregnant sheep of water improves energy metabolic parameters, and the use of this substance its very important to minimize the negative energy balance at the end of pregnancy.
A suplementação com propilenoglicol melhora o metabolismo energético em ovelhas gestantes
Keywords: Glucose; NEFA; Pregnancy; Sheep; Triglycerides